Educational fields of higher education graduates in European Union - Angheluță, Petrică Sorin; Dobrea, Cătălin Răzvan; Crețu, Florentina Raluca; Ganea, Otilia; Breaz, Teodora Odett; Popescu (Groaznicu), Nicoleta Luminița (Frontiers in Environmental Science, 2023)
The processes of automation and globalization, through their changes, are resizing jobs. A picture of the labor market can be provided by the educational fields of the graduates. Thus, depending on the educational field, the situation regarding the distribution of bachelor's graduates is analyzed in the article. The importance of the quality of the education and vocational training processes can be considered to be the basis of addressing the major challenges that are manifesting worldwide. Economic and social pressures influence the development of skills and competences including for higher education. Also, training for the purpose of employment is responsible for increasing employability. The degree of access to jobs is higher in situations where the level of education is higher. For the 15-64 age group, the article presents the share of graduates with an education level between 5 and 8. Quality education can contribute to sustainable development. Thus, in a community, to identify solutions to problems that may arise, the contribution of education can increase by increasing the quality of life of the members of that community. In this context, for the 30-34 age group, at the European level, the evolution of graduates with a tertiary level of education is analyzed.